2018
DOI: 10.1111/sjop.12444
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with life in individuals with a lower limb amputation: The importance of active coping and acceptance

Abstract: The aim of this study was to analyze the relationship between sociodemographic/clinical characteristics, coping strategies and satisfaction with life in individuals with lower limb amputation. Sixty-three individuals with a lower limb amputation due to Diabetes and Peripheral Vascular Disease participated in the study and answered measures of coping strategies and satisfaction with life. Findings revealed high dissatisfaction with life. Acceptance and active coping were the most used coping strategies. Satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
(87 reference statements)
0
7
0
1
Order By: Relevance
“…Inconsistent with these findings, however, are sporadic reports of ATC, and in particular denial coping, being independent of psychosocial outcomes (e.g. Classen et al, 1996; Duangdao and Roesch, 2008; Pereira et al, 2018; Tomberg et al, 2005).…”
mentioning
confidence: 92%
“…Inconsistent with these findings, however, are sporadic reports of ATC, and in particular denial coping, being independent of psychosocial outcomes (e.g. Classen et al, 1996; Duangdao and Roesch, 2008; Pereira et al, 2018; Tomberg et al, 2005).…”
mentioning
confidence: 92%
“…[5][6][7] A growing body of literature focuses on the types of coping strategies (e.g., active coping and passive coping) that are associated with health outcomes among individuals with physical disabilities. [8][9][10][11] Previous findings have provided evidence that active coping strategies can lead to better positive adjustment and psycho-social outcomes among individuals with disabilities and illnesses, whereas avoidance or passive forms of coping predict increased psychological distress and diminished mental health. [12][13][14] For example, Livneh and Martz 8 showed that individuals with spinal cord injuries who used active engagement in coping strategies (e.g., positive reframing, acceptance seeking social support) experienced better psycho-social adjustment and quality of life outcomes than those who did not.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy may be due to cultural differences in thinking style. Coping research has consistently identified the stress-buffering role of active coping in Western countries (e.g., [47,48]), and the adoption of this direct action-oriented strategy matches the linear thinking style that is prominent among Westerners [49].…”
Section: Non-significant Active Coping-physical Health Associationsmentioning
confidence: 97%